2017
DOI: 10.1149/2.0501712jes
|View full text |Cite
|
Sign up to set email alerts
|

Surface Area Increase of Silicon Alloys in Li-Ion Full Cells Measured by Isothermal Heat Flow Calorimetry

Abstract: Li-ion pouch cells utilizing a negative electrode formulated with 15 wt% of an engineered Si alloy in a graphite composite electrode were cycled in an isothermal heat flow calorimeter against a LiCoO 2 positive electrode. Two different electrolytes were investigated: a blend of ethylene carbonate and ethyl methyl carbonate (3EC:7EMC) and a blend of ethylene carbonate, ethyl methyl carbonate and 1-fluoro ethylene carbonate (27EC:63EMC:10FEC). Both electrolytes were 1 M in LiPF 6 salt. The parasitic thermal powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 15 publications
5
38
0
Order By: Relevance
“…Since the bimodal curve shape distribution is visible on both the charge and discharge data, we believe that these minute variations highlight the necessity to produce larger arrays of cells as they would have otherwise likely not been captured. Comparing the herein acquired data to that found in literature on LNO the region showing increased variance that is denoted by the roman numeral I in Figure 4 could be attributed to the H1 and H1 to H2 phase transition or more likely to the insertion into Si in the Si-C anode 22 . Since there is some considerable variance in Si-particle loading (see SI) across the anode sheets we believe this variance to be originating from the electrodes and not necessarily from assembly or randomness.…”
Section: Formation Cyclessupporting
confidence: 73%
“…Since the bimodal curve shape distribution is visible on both the charge and discharge data, we believe that these minute variations highlight the necessity to produce larger arrays of cells as they would have otherwise likely not been captured. Comparing the herein acquired data to that found in literature on LNO the region showing increased variance that is denoted by the roman numeral I in Figure 4 could be attributed to the H1 and H1 to H2 phase transition or more likely to the insertion into Si in the Si-C anode 22 . Since there is some considerable variance in Si-particle loading (see SI) across the anode sheets we believe this variance to be originating from the electrodes and not necessarily from assembly or randomness.…”
Section: Formation Cyclessupporting
confidence: 73%
“…3 Figures 2a and 2b show the parasitic thermal power and coulombic inefficiency (CIE = 1-CE) of a cell containing CO 2 charged by the dry ice method and a cell with 10 wt% FEC in the base electrolyte. These cells were cycled 50x and 42x respectively before they were inserted into the calorimeter.…”
Section: Microcalorimetry and Imaging-mentioning
confidence: 99%
“…While there can be several reasons for the inferior cycle life of silicon and silicon alloys one important contributor to poor cycle life is the erosion of the silicon particle by parasitic electrolyte reactions. [1][2][3] Because of the volume changes Si experiences during cycling, continuous passivation is required at the surface and the demands on the electrolyte system are greater than for graphite.Carbon dioxide (CO 2 ) has been described as an effective electrolyte additive in metallic Li cells many years ago. 4 In that work it was shown that cycling efficiencies of the Li electrode were greatly increased in the presence of CO 2 .…”
mentioning
confidence: 99%
“…31 IMC has been used to study the role of carbon dioxide on the formation of SEI with a silicon anode. 32 Further, IMC was previously utilized to study battery systems containing 15 wt % engineered Si alloy 33 and 20 wt % nano silicon composite anodes in full and symmetric cells, respectively. 34 In the prior reports, the parasitic heat evolution was probed at high cycle number where the entropic contributions to heat flow were neglected, as entropy changes during discharge and charge were assumed to be reversible.…”
Section: Introductionmentioning
confidence: 99%